The ‘Seamless Web’: The Development of the Electronic Patient Record in Aarhus Region, Denmark - Jensen, C. B. (Methods of Information in Medicine, 2003)
Objectives: The article surveys the organization of the current project to develop an electronic patient record in the Aarhus Region, Denmark.Methods: The article is based on various policy documents and reports as well as a number of semi-structured interviews with project managers from the EPR organization in Aarhus County and with participants in the development process at local hospitals. This material is used to present and discuss the framing of the project in a ‘discourse coalition’. Results: The stabilization of a specific discourse coalition has been an important factor in ensuring the success of the development project up to the present moment. This coalition became relatively stable by integrating a diverse set of actors in a story-line about the relationships between cooperation, management and technology in the medial sector, and has influenced the modular organization of the project.Conclusions: The successful maintenance of the discourse coalition allows the project to appear ‘seamless’ from the outside. Conversely, the project is likely to be continually reviewed as successful only to the extent that it is able to flexibly keep the fluctuating set of relevant actors in alignment. If the practical work of keeping a coalition in place remains invisible it becomes easy to imagine an ideal way of planning large socio-technical projects, like developing an ECR. But practical success is more likely to be achieved if one takes seriously the thorough intertwining of discursive, organizational and technical aspects of development projects.
Keywords: Electronic patient record; organization; development project; discourse coalition